Effect of additives on chia mucilage suspensions: A rheological approach. (December 2020) - Cuomo, Francesca; Iacovino, Silvio; Cinelli, Giuseppe; Messia, Maria Cristina; Marconi, Emanuele; Lopez, Francesco
Abstract: Due to the benefits deriving from its composition, chia seed mucilage is an emerging resource in food industry applications. In food processing, the combination of different physical-chemical parameters is encountered; therefore, a thorough knowledge of the effect of these parameters on the raw material is required. In this contribution, starting from the effect of temperature and pH on the rheological properties of chia mucilage suspensions, the influence of ionic strength and time were considered together with the addition of stabilizing molecules. The rheological analysis performed on mucilage suspensions showed a plastic behaviour of the fluid. Among the parameters considered, the increase of temperature and ionic strength cause a decrease in the apparent viscosity of mucilage suspensions. Apparent viscosity is also strongly influenced by the time and ionic strength. In the presence or in the absence of salts, indeed, a decrease in the consistency index is observed during suspensions storage. This evidence indicates that the suspensions are not stable. Having associated this aspect with auto-oxidative phenomena, different additives were added to the suspensions. The addition of glycerol only partially attenuates the natural degradation tendency of chia mucilage. The addition of a hydrophilic antioxidant has positive effects at low concentration while the presence of a hydrophobic antioxidant is more effective for stabilizing mucilage. Graphical abstract: Image 1 Highlights: Ionic strength and temperature influence the viscosity of mucilage suspensions. Viscosity of chia mucilage suspensions decreases within time. Low concentrations of ascorbic acid and essential oil stabilize the mucilage.